Artikel e-Health Method “Malaria and Pregnancy” Early Detection and Prevention of Malaria in Pregnancy - Kapitan, Meiyeriance; Beta, Mariana Oni; Selasa, Pius; Mulhaeriah, Mulhaeriah; Meme, Modesta Y (Window of Health : Jurnal Kesehatan, 2023)
Malaria is a tropical disease and a health problem in East Nusa Tenggara (NTT) Province. Malaria cases have decreased in the last ten years (2006-2015), namely 71 percent, but there are still cases of malaria that tend to increase in four districts on Sumba Island. Highly endemic districts are in Southwest Sumba, West Sumba, and East Sumba, with a total of 4.119 cases, 1443 and 4273 in November 2022. Most cases of malaria are in the age group of children, toddlers, and pregnant women. This group is very risky and harms the condition of pregnant women and their fetuses. The health promotion intervention the researchers provided was an e-health application, “Malaria and Pregnancy,” for early detection and prevention of malaria during pregnancy. This study aims to determine the effect of the e-health model in the prevention and early detection of malaria in pregnancy. This research method is quantitative with a quasi-experimental pre-post test design in two groups. The respondents in this study were determined using a systematic sampling approach with a sample of 100 pregnant women. The research location is in Southwest Sumba. This research went through the stages of ethical testing, instrument trials, data normality tests, descriptive tests, and different tests. The results of this study used the chi-square statistical test to show that respondents' knowledge and behavior about malaria detection and prevention using the eHealth Malaria and Pregnancy method differed from respondents who did not receive the intervention (p=0.001) and (p=0.00). The instruments of this study are useful as educational tools for pregnant women to avoid malaria. To optimize the application, further research, such as telemedicine and telehealth, is necessary